EMPOWERMENT THROUGH THE DEVELOPMENT OF TOURISM VILLAGE IN JENGGALA VILLAGE, TANJUNG DISTRICT NORTH LOMBOK DISTRICT - Marjadi Marjadi; Mohammad Jomail; Ajuar Abdullah (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
Study this aim for knowing efforts made _ for empower Public through Development Village Village Tour _ Jenggala as well as knowing role active Kadin Republic of Indonesia can restore economy the resulting community by disaster earthquake on A devastating 2018 house and economy they Type study this is descriptive with approach qualitative . Informant study Among other Head Institution Training Work Intesa Yogyakarta as companion empowerment trusted community _ Indonesian Chamber of Commerce , Head of Village Jenggala , Chief Pokdarwis and community ( perpetrators ) travel ). Instrument study is researcher alone . Technique data analysis with method data collection through observation , interview and documentation and next Data Condensation that is After the researcher collected the data, the data was then analyzed. The raw data that has been found is carried out through a process of selecting, centralizing, simplifying, and transforming into summaries, tables, and figures according to the focus of this research. Results study show that activity empowerment Public through development village Village tourism _ Jenggala among others: 1). Help development infrastructure , including house with each one room vavilium for for rent to guest , hall , room bath , prayer room , angkringan , cage communal and others _ all given help by Room Dangang and Industry ( Kadin ) of the Republic of Indonesia; 2). Help mentoring , training language foreign , welcoming guest , house keeping , culinary , bookkeeping about tourism , structure organization and management manager tour village ; 3). Strengthening institutional , pokdarwis and secretarial manager village tour Jenggala ( Tasola Beach Village ), government Village Jenggala , District Cape , government area North Lombok Regency and North Lombok Regency BUMD ; 4). Strengthening partnership Among community , government , BUMD and private that is government Village Jenggala , Service Tourist North Lombok Regency , college high , organization field rescue , PLN , Indosat and other . Supporting factor of them is potency abundant tourism , accommodation _ with population local already available , cheer up and response positive from community , as well as help from Kadin Republic of Indonesia. While the inhibiting factors that appear that is the quality of human resources that are still low and unprofessional, not yet there is regulation and governing policy _ about village tour specifically Village Tour Jenggala and recording tourism that has not clear .